2015
DOI: 10.1016/j.jcrs.2015.10.040
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond laser–assisted compared with standard cataract surgery for removal of advanced cataracts

Abstract: Drs. Hatch, Talamo, and Dick are consultants to Abbott Medical Optics, Inc. Dr. Schultz has no financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 15 publications
2
25
1
4
Order By: Relevance
“…This study mirrored previously reported findings with regard to the safety and visual outcomes achieved when comparing FLACS to conventional phacoemulsification . Although the numbers included in this study are small, this is the first to demonstrate this finding in a post‐vitrectomy setting.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This study mirrored previously reported findings with regard to the safety and visual outcomes achieved when comparing FLACS to conventional phacoemulsification . Although the numbers included in this study are small, this is the first to demonstrate this finding in a post‐vitrectomy setting.…”
Section: Discussionsupporting
confidence: 86%
“…This study mirrored previously reported findings with regard to the safety and visual outcomes achieved when comparing FLACS to conventional phacoemulsification. 3,[7][8][9][10]14,18,19 Although the numbers included in this study are small, this is the first to demonstrate this finding in a post-vitrectomy setting. The difference in posterior capsular opacification rate reported in this study is likely secondary to a difference in the length of follow-up between the two groups, with the conventional Figure 2.…”
Section: Discussionmentioning
confidence: 67%
“…However, some patients may not be suited to FLACS or to a high-volume service, although the number of contraindications for FLACS is decreasing as experience with the technology improves. [21][22][23] Departmental costs used in this model were obtained from a retrospective review of the financial records at four NHS foundation trusts. In order to ensure that the results were applicable to more than just one hospital with its associated population, we selected two teaching hospitals and two district general hospitals of varying sizes, with annual numbers of between ∼1400 and 5000 cataract operations.…”
Section: Discussionmentioning
confidence: 99%
“…In eyes with LOCS III grade 3 cataracts, EPT ranged from 0.46 to 3.10 s (mean 1.38) in the phaco group while it was zero in the laser group. In eyes with grade 4 brunescent cataracts, EPT was 2.12 to 19.29 s (mean 6.85) in the phaco group and 0 to 6.75 s (mean 1.35) in the laser group [40]. …”
Section: Lcs In Challenging Casesmentioning
confidence: 99%